High-resolution geochemical record of environmental changes during MIS 3 from the northern Alps (Nesseltalgraben, Germany). (15th August 2019) - Mayr, Christoph; Stojakowits, Philipp; Lempe, Bernhard; Blaauw, Maarten; Diersche, Volker; Grohganz, Madleen; Correa, Matthias López; Ohlendorf, Christian; Reimer, Paula; Zolitschka, Bernd
Abstract: Ravine slopes at the recently discovered Nesseltalgraben site in southeastern Germany provide a unique last glacial sediment record for the Northern Calcareous Alps. The 21 m-long profile is dominated by fine-grained lacustrine-palustrine sediments overlain by several metres of glacifluvial gravels and lodgement tills of the Last Glacial Maximum and underlain by a diamicton. The age model includes 29 radiocarbon analyses and one paleomagnetic anomaly (Laschamp event) together providing a modelled age range from c . 59 to 29.6 ka cal BP, i.e. Marine Isotope Stage (MIS) 3. Apart from a description of the lithofacies, X-ray-fluorescence (XRF) scanning and elemental analyses provide high-resolution records of the geochemical composition. Multivariate analyses of XRF data separate Ca from other major elements. Carbonate contents, represented by Ca and total inorganic carbon, reach maxima in repeatedly occurring calcareous silty to sandy layers and are related to glacigenic origin. These indicate repeated inner-alpine local glaciations during stadials of MIS 3. Scanning electron microscopy and XRF data confirm the detrital origin of these layers. In contrast, organic matter and elements more resistant to chemical weathering (Si, Ti, Zr) accumulated during interstadials and concurrently elevated Rb/Sr ratios indicate intensified weathering. The high-frequency proxy variations determined for Nesseltalgraben reflect interstadial-stadial climate variability comparable with oxygen-isotope records from Greenland ice cores and Alpine speleothems. Thus, Nesseltalgraben is among the very few independently dated sediment records from continental Europe covering the entire MIS 3 and reflecting the full Dansgaard-Oeschger climate variability. Highlights: A 21 m sediment profile from the northern Alps provides a complete MIS 3 record. Repeated inner Alpine glaciations are indicated by calcareous silt layers. Geochemical variations reflect interstadials and stadials. The Nesseltalgraben record resembles Dansgaard-Oeschger climate variability.